Braci mniejszych większy sens. Zwierzę w wierszach Georga Trakla i Bolesława Leśmiana - Kołodziej, Dorota (Zoophilologica. Polish Journal of Animal Studies, 2020)
Georg Trakl as well as Bolesław Leśmian used poetry to question about peoples’ relationship with the world and both of them noticed that – as Tadeusz Sławek in the article Ratujące niebezpieczeństwo postsekularyzmu wrote – “human could be saved or redeemed only thanks to something which is nonhuman and associated with animal or God.” This statement is for me the Anzatspunkt and allows to compare a poem entitled W locie by Bolesław Leśmian and a mysterious blaues Wild figure in Trakl’s pieces. This article attempts to show specific identity of an animal, which is usually defined as the other being. It is possible to observe this factor also on the language basis. The name “animal” – as Jacques Derrida noticed – violent by itself, is a harmful category. Leśmian’s godlike creature and blaues Wild are not easy to describe – they make readers attentive to the text. This article attempts to analyse this problematic animal noun, because without understanding its nature it might be also impossible to solve the issue what “humane” and “divine” mean.